A fact‐finding survey on self‐efficacy of foot care behaviour in patients with diabetes: Analysis using the Diabetes Study from the Center of Tokyo Women's Medical University 2017 (DIACET 2017). Issue 2 (19th December 2020) - Ikura, Kazuki; Kato, Hayato; Azuma, Haruna; Oda, Yuri; Kato, Yuka; Miura, Junnosuke; Babazono, Tetsuya
Abstract: Aim: We aimed to determine the association between self‐efficacy of foot care behaviour and chronic complications in Japanese patients with diabetes. Methods: We conducted a cross‐sectional study based on a questionnaire survey of 4571 patients with type 1 and type 2 diabetes who had (a) given consent to participate in the Diabetes Study from the Center of Tokyo Women's Medical University: DIACET 2017, and (b) completed all the questions of the Japanese Version of Foot Care Confidence Scale (J‐FCCS), consisting of 12 statements. Results: A greater proportion of respondents answered that they were not confident in determining the condition of corns and/or calluses and the condition of toenails. The J‐FCCS total scores of the patients with retinopathy ( p  <.001) and numbness or pain in the feet ( p  <.001) were significantly lower than those of the patients without these complications. In both the multiple regression analysis and logistic regression analysis, lower J‐FCCS was significantly associated with retinopathy and numbness or pain in the feet. Conclusion: Foot care education that emphasizes a psychological approach in improving confidence associated with foot self‐care is important for patients with advanced complications of diabetes. Abstract : We conducted this large study to clarify the association between self‐efficacy of foot care behaviour and microvascular complications in patients with type 1 and type 2 diabetes, using the Japanese version of the FCCS (J‐FCCS). The multiple regression analysis showed that retinopathy and numbness or pain in the feet, but not CKD, were significantly associated with lower J‐FCCS total scores.